Effects of Coenzyme Q10, Fullerene C60, and ?lpha-Lipoic Acid on Histomorphometric, Antiapoptotic and Insulin Expression in Pancreatic Tissue of Rats Exposed to Bisphenol A - Çerıbası, Songül; Yüce, Abdurrauf; Bulmus, Ozgur (My University, 2024)
The aim of this study was to determine the morphometric changes in the pancreas, apoptosis related pancreatic damage, and differences in insulin expression in male rats exposed to low doses of BPA from early pubertal development and to determine the possible protective effects of CoQ10, FUL, and ALA against the effects of BPA. Sixty, one-month-old male Sprague-Dawley rats were used and divided into 8 groups. The groups were administered BPA, CoQ10, FUL, ALA in 0.2 mL olive oil for 7 weeks. Morphometric measurements of islets of Langerhans in all groups showed that the mean islet number, islet diameter, and area decreased in the BPA group. Administration of CoQ10 and ALA together with BPA caused an increase in islet numbers, while FUL was not effective. CoQ10 and FUL were ineffective against BPA, but ALA had a positive effect on islet diameter and area. Insulin positivity decreased in all BPA-treated groups compared to the control, and insulin expression in islets was not significantly affected by CoQ10, FUL, and ALA against BPA. CoQ10 and ALA were effective against the apoptotic changes induced by BPA, but FUL had no positive effect. In conclusion, while long-term administration of BPA in rats did not result in histopathological changes in the endocrine pancreas, the study revealed significant morphometric alterations, a reduction in insulin secretion within the islet cells, and an increase in apoptosis. We determined that CoQ10 and ALA had partial protective effects against the impact of BPA on the endocrine pancreas.
Keywords: Pancreas; coenzyme Q10; Alpha-lipoic acid; bisphenol A; fulleren C60